Analysis of sensorineural hearing loss in patients attending an otolaryngology clinic in North Central Nigeria - Nuhu D. Ma'an; Ishaku Turaki; David Shwe; Bulus Nansak; Benjamin Babson; Simji Gomerep; Lauren Malaya; David Moffatt; Nasim Shakibai; Slobodan Paessler; Tomoko Makishima; Nathan Y. Shehu (Public Library of Science (PLoS), 2023)
Hearing loss is the third leading cause of years lived with disability. Approximately 1.4 billion people have hearing loss, of which 80% reside in low- and middle-income countries with limited audiology and otolaryngology care available to them. The objective of this study was to estimate period prevalence of hearing loss and audiogram patterns of patients attending an otolaryngology clinic in North Central Nigeria. A 10-year retrospective cohort study was carried out analyzing 1507 patient records of pure tone audiograms of patients at the otolaryngology clinic at Jos University Teaching Hospital, Plateau State, Nigeria. Prevalence of hearing loss of moderate or higher grade increased significantly and steadily after age 60. Compared to other studies, there was a higher prevalence of overall sensorineural hearing loss (24-28% in our study compared to 1.7-8.4% globally) and higher proportions of the flat audiogram configuration among the younger age patients (40% in younger patients compared to 20% in patients older than 60 years). The higher prevalence of the flat audiogram configuration compared to other parts of the world may be suggestive of an etiology specific to this region, such as the endemic Lassa Fever and Lassa virus infection in addition to cytomegalovirus or other viral infections associated with hearing loss.